FAILURE TO BECOME A TNI SOLDIER: A PENOMONOLOGICAL STUDY OF YOUTH ASPIRATIONS IN INDONESIA: Kegagalan Menjadi Prajurit TNI: Studi Penomonologi Cita-Cita Pemuda di Indonesia - samsul arifin; Jefri Mailool (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Failure is a situation where someone is unable to achieve their desires or achieve their desired goals. There are many ways to deal with failure for someone who experiences failure. This study aims to determine how young people respond to failure and shift the form of failure from TNI Soldiers to professions outside the TNI Soldier. This study uses a qualitative phenomenological approach. Ten Respondents were randomly selected from different regions. Data collection techniques used were through interviews and analysis techniques through Creswell's steps, from organizing data to presenting and visualizing it with the help of Atlas TI software. The results showed that those who had experienced failure to become TNI Soldiers responded almost uniformly to negative and positive responses. Negative responses mostly mentioned a lack of transparency in the selection process and the absence of support and "backing". Meanwhile, positive responses, Respondents realized that success requires hard work and long preparation. Sincerity, patience, acceptance of circumstances and enthusiasm in seeking alternative professions outside the TNI Soldier, and belief in God's destiny were forms of self-evaluation of the Respondents. The results of this study are expected to help young people in Indonesia who want to become TNI soldiers, on how to prepare themselves and how to respond if they fail to achieve their dreams..